Investigating the Spatial Relationship between the Upstream Gauging Stations and the Reservoi - Abdul Mokhtar, Suriyati (2016)
﻿operation involves many critical decisions due to unpredicted circumstances, such as drought or flood. The reservoir water rclcase deciqion is one of the challenging tash for the reservoir operator since the decision tn deal with many complicated dccision variables and mu!tipurpose operation. Typically, thc watcr that now into the reserroir cumes from the upstream rivcr network. The gru~in~stations are locatcd at diffcrent locatinns and the distancc bctween the gauging stations and the rescrvnir are varied. This information indiratcs that there are spatial relntionships between gauging stations and reservoir.This paper aims to investigate the spatial miationship belhvecn the upstrcam gauging stntions and the reservoir by mapping temporal rainfall information on each gauging station with the resclvoir watcr levcl, The mapping was estahlishcd using Rackpropagatian Neural Network The findings show that dintrent location and distancc of tach gauging station with tl~c Timah 'Tssoh reservoir docs affect thc water travcl time from gauging stations to thc rcscrvoir.